Expertise affects representation structure and categorical activation of grasp postures in climbing - Bläsing, Bettina E.; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Frontiers in Psychology, 2014)
In indoor rock climbing, the perception of object properties and the adequate execution of grasping actions highly determine climbers’ performance. In two consecutive experiments, effects of climbing expertise on the cognitive activation of grasping actions following the presentation of climbing holds was investigated. Experiment 1 evaluated the representation of climbing holds in the long-term memory of climbers and non-climbers with the help of a psychometric measurement method. Within a hierarchical splitting procedure subjects had to decide about the similarity of required grasping postures. For the group of climbers, representation structures corresponded clearly to four grip types. In the group of non-climbers, representation structures differed more strongly than in climbers and did not clearly refer to grip types. To learn about categorical knowledge activation in Experiment 2, a priming paradigm was applied. Images of hands in grasping postures were presented as targets and images of congruent, neutral, or incongruent climbing holds were used as primes. Only in climbers, reaction times were shorter and error rates were smaller for the congruent condition than for the incongruent condition. The neutral condition resulted in intermediate performance. The findings suggest that perception of climbing holds activates the commonly associated grasping postures in climbers but not in non-climbers. The findings of this study give evidence that the categorization of visually perceived objects is fundamentally influenced by the cognitive-motor potential for interaction, which depends on the observer’s experience and expertise. Thus, motor expertise not only facilitates precise action perception, but also benefits the perception of action-relevant objects.